MNCTV Reporters Professionalism in Covering and Writing News on the 2024 Regional Head Elections (Pilkada) in Indonesia - Arifin Saleh Harahap; Andry Susanto; Erna Febriani; Dzakwan Amar Zuhdi; Ballian Siregar; Fajarina Fajarina; Euis Nurul Bahriah (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to test the professionalism of MNCTV reporters in covering and writing news, focusing on knowledge, skills, and work ethics. The theory used in this study is the establishment of a media agenda to further criticize the editorial policy on reporting assignments to reporters. The research method used is a qualitative case study. The results of the study show that MNCTV reporters are quite professional in covering and writing news, although there are some things that deserve to be criticized. The news presented still contains many ceremonial activities related to regional elections, such as visits to the community and the dissemination of campaign promises. News that criticizes the weaknesses of regional candidates is still less prominent. In fact, news like this is very important for viewers to know so that it can be a reference material in choosing the best regional head candidate. Every contestant in a campaign always tends to spread promises. Ideally, MNCTV reporters criticize such promises as balanced social control when covering and writing news